"Who Should Care about Our Children?": Public Childcare Policy in Yugoslav Socialism and Its Serbian Aftermath. (April 2019) - Simic, Marina; Simic, Ivan
This study explores public childcare policies in socialist Yugoslavia and their postsocialist transformation in Serbia. Focusing on gender regimes of the state provided childcare, we examine how they reflect ideology of availability of public childcare facilities—crèches and kindergartens. Basing our work on archival sources, interviews, and ethnographic material, we show that despite the socialist state's ideology of gender equality, women continued to be primary caregivers, while the female kinship networks acted as an additional safety net due to unavailability of childcare facilities. This article reveals long-term patterns of childcare practices, only slightly altered with the fall of socialism.